1998
DOI: 10.1021/bi9815041
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Activation of Acyl-CoA Substrates by Medium Chain Acyl-CoA Dehydrogenase:  Interaction of the Thioester Carbonyl with the Flavin Adenine Dinucleotide Ribityl Side Chain

Abstract: The flavin adenine dinucleotide (FAD) cofactor of pig kidney medium-chain specific acylcoenzyme A (CoA) dehydrogenase (MCADH) has been replaced by ribityl-3′-deoxy-FAD and ribityl-2′-deoxy-FAD. 3′-Deoxy-FAD-MCADH has properties very similar to those of native MCADH, indicating that the FAD-ribityl side-chain 3′-OH group does not play any particular role in cofactor binding or catalysis. 2′-Deoxy-FAD-MCADH was characterized using the natural substrate C 8 CoA as well as various substrate and transition-state an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 41 publications
6
65
0
Order By: Relevance
“…The corresponding distances in MCAD are also 2.8 and 2.9 Å, respectively (14). These interactions are not only responsible for proper orientation of the substrate, they are also crucial for polarization of the substrate and the lowering of the pK a of the C-2 proton for abstraction by the catalytic base, Glu-376 (32). A water molecule is conserved in the binding cavity of all IBD subunits and is also present in the SCAD binding cavity.…”
Section: Resultsmentioning
confidence: 98%
“…The corresponding distances in MCAD are also 2.8 and 2.9 Å, respectively (14). These interactions are not only responsible for proper orientation of the substrate, they are also crucial for polarization of the substrate and the lowering of the pK a of the C-2 proton for abstraction by the catalytic base, Glu-376 (32). A water molecule is conserved in the binding cavity of all IBD subunits and is also present in the SCAD binding cavity.…”
Section: Resultsmentioning
confidence: 98%
“…However, several enzymes have been identified (3,(5)(6)(7)(8) in which the 2Ј-hydroxyl of the ribityl chain appears to play an important role augmenting the redox chemistry. PHBH clearly belongs to this group of enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The redox properties of the free artificial flavin are virtually identical to those of natural flavin (3), suggesting that the introduction of a probe nucleus at the ribityl 2Ј-position has no significant effect on flavin solution chemistry. Surprisingly, although the fluorine probe is chemically isolated from the isoalloxazine reaction center, the catalytic and redox properties of several flavoenzymes are significantly different when the natural flavin is replaced with the 2Ј-F arabino analog or other 2Ј-derivatives (3)(4)(5)(6)(7)(8). These important changes indicate that the 2Ј-hydroxyl of natural flavins plays an important chemical role as a hydrogen-bonding active site substituent much like a serine residue might.…”
mentioning
confidence: 99%
“…This mode of substrate binding seems to be a general feature of all described crystal structures of Acds (1). Engst et al showed previously that the 2=-OH group not only promotes the initial ␣C-H deprotonation in MCAD but also supports proper substrate orientation (69). Hence, we propose that the cofactor is stabilizing the quaternary structure of Acd DPN7 and is necessary for correct positioning of 3SP-CoA.…”
Section: Figmentioning
confidence: 53%